EDITORIAL - Vargas, J. V. C. (Revista de Engenharia Térmica, 2018)
The editorial of Engenharia Térmica of this issue continues the discussion on scientific research needs in vital areas in which thermal engineering has important participation. The main goal is to motivate the readers, within their specialties, to identify possible subjects for their future research. In the beginning of the 21st century the international scientific community pointed out that there was a need for increased push towards alternative energy technologies to replace fossil and nuclear sources in the near future, in order to determine what is scientifically possible, environmentally acceptable and technologically promising. Also, the scientists recalled that policy, science and technology need to work together harmoniously, which are responsible for acceptability, possibility and practicability, respectively. A great amount of diversity with the exploration of innovative nanomaterials and their hybrid assemblies for energy conversion and storage have been seen in energy research. Advances in time-resolved spectroscopy, surface science, imaging techniques, and various in situ and operando characterization techniques are providing new insights into energy conversion and storage processes. The same challenges continue to be up-to-date as discussed by the scientific community recently, showing that technically and economically viable renewable energy generation and storage are major hurdles to be overcome. For that, some research areas that need to be pursued in the energy field were listed: energy materials; electrochemical energy conversion and energy storage; solar cells; solar fuels; LED and display devices, and last but not least theory and computational modeling. Such areas represent a few potential opportunities, which in the opinion of Engenharia Térmica have the potential for important scientific advances. The mission of Engenharia Térmica is to document the scientific progress in areas related to thermal engineering (e.g., energy, oil and renewable fuels). We are confident that we will continue to receive articles’ submissions that contribute to the progress of science.